2005
DOI: 10.1002/cncr.21172
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence physicians' detection of distress in patients with cancer

Abstract: Objective In vitro observations and studies in murine experimental autoimmune encephalomyelitis (EAE) have shown protective effects of sodium channel blockers on central nervous system axons and improved clinical status when treatment is continued throughout the period of observation. Several clinical studies of sodium channel blockers are under way in patients with multiple sclerosis. Here we asked whether a protective effect would persist after withdrawal of a sodium channel blocker. Methods We studied a mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Five studies found a correlation between training (or years of training) and communication (or patient outcome) [18,27,30,36,42]. Clinician and patient agreement for patient decision-making preferences increased with years of clinician training [42].…”
Section: Clinician Age Experience and Specific Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies found a correlation between training (or years of training) and communication (or patient outcome) [18,27,30,36,42]. Clinician and patient agreement for patient decision-making preferences increased with years of clinician training [42].…”
Section: Clinician Age Experience and Specific Trainingmentioning
confidence: 99%
“…It had no effect on indication for chemotherapy [35] or on communication concerning health-related quality of life (HRQL) [28]. It had no influence on the concordance between clinician and patient perceptions of patient distress and need for support [36,41] or on patient perception of care, information exchange, affective behavior, coordination, or health promotion [23]. In addition, gender was not associated with responses to empathic opportunities.…”
Section: Clinician Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…10, 11 Certain provider behaviors have been shown to elicit these concerns: open-ended questions, allowing more time for patients to speak, and empathy (Table 1). 1215 Open questions such as “How are you doing with all of this?” or “Is there something else you’d like to talk about today?” 16 let patients know that their doctor will be willing to listen. Patients also give “cues” to providers about their concerns, for example, “I’m not sure what the treatment options are.” [cue for information] or “That’s one thing I have as a big fear.” [cue for emotional exploration and support].…”
Section: Core Communication Skillsmentioning
confidence: 99%
“…Many studies worldwide have explored cancer survivors' psychosocial rehabilitation needs [9][10][11][12][13], but little, if any, has been conducted in China. International studies about cancer survivors' psychosocial needs indicate a desire for ongoing psychological counselling, a lack of availability of complementary and alternative therapies, a need for continuous support, for information about rehabilitation possibilities and for support to the family and need for social support [8][9][10][11][12][13]. However, peoples' social and cultural backgrounds have substantial impact on their attitude towards cancer and its causes and on treatment options [14].…”
mentioning
confidence: 99%